Optimizationfrench Fries Production Using the Just in Time Method in The Inventory Management Cost System at The Coral (Bar and Resto) in Fodo Village, Gunungsitoli City - Laowo, Ridho Tri Aman; Buulolo, Nanny Artatina; Harefa, Idarni; Gea, Jeliswan Berkat Iman Jaya (PT. Maju Malaqbi Makkarana, 2025)
This research is motivated by the consequences of the raw material ordering method which is still subjective, namely based on visual estimates without a structured system. This results in The coral experiencing a decrease in revenue and losses. The purpose of this study is to find out how the inventory management system at The coral in Fodo Village, Gunungsitoli City, To find out the application of the Just-In-Time method in the potato raw material inventory management system increases the efficiency of producing French fries, To find out how the effectiveness of the Just-In-Time method in reducing raw material waste and ensuring optimal raw material availability for producing French fries at The coral. This study uses a quantitative research approach, namely a research method that emphasizes objective measurements and statistical analysis of numerical data to test the established hypothesis. This study uses a company method approach and a just-in-time method that aims to test the independent and dependent variables between the company method and the just-in-time method. Thus, from the comparison of the two methods above, it can be concluded that purchasing raw potato raw material inventory using the just-in-time method at The coral can minimize raw material inventory according to production needs, to avoid damage to raw material stocks that affect the quality of raw materials such as potatoes that are easily damaged.